INCREASING MOTIVATION AND SCIENCE LEARNING OUTCOMES THROUGH THE USE OF LEARNING MEDIA FOR CLASS 5 STUDENTS - Dela Dwi Rukmala; Agung Setyawan (Citra Dharma Cindekia, 2022)
Learning media is a means used in delivering information from teachers to students during the learning process. The purpose of this study was to determine the effectiveness of the use of learning media on students' motivation and learning outcomes, especially in science subjects about Changes in Objects in the fifth grade of elementary school. This research can be categorized as Participatory Action Research (PAR), where the data management in this study uses qualitative and quantitative data analysis which is analyzed by descriptive method. Based on the results of these studies, it is clear that the use of learning media in the learning process greatly influences students' motivation and learning outcomes where higher learning outcomes are obtained by utilizing learning media with an average that can be exceeded by all students with scores above the average obtained by each. -each student. Therefore, it is hoped that educators will be able to develop more creative and innovative learning media so that learning objectives can be carried out properly and are able to create meaningful learning for students.